Glucagon-like peptide-1 receptor agonists and sodium-glucose cotransporter 2 inhibitors, anti-diabetic drugs in heart failure and cognitive impairment: potential mechanisms of the protective effects - Riemma, Maria Antonietta; Mele, Elena; Donniacuo, Maria; Telesca, Marialucia; Bellocchio, Gabriella; Castaldo, Giuseppe; Rossi, Francesco; De Angelis, Antonella; Cappetta, Donato; Urbanek, Konrad; Berrino, Liberato (Frontiers in Pharmacology, 2024)
Heart failure and cognitive impairment emerge as public health problems that need to be addressed due to the aging global population. The conditions that often coexist are strongly related to advancing age and multimorbidity. Epidemiological evidence indicates that cardiovascular disease and neurodegenerative processes shares similar aspects, in term of prevalence, age distribution, and mortality. Type 2 diabetes increasingly represents a risk factor associated not only to cardiometabolic pathologies but also to neurological conditions. The pathophysiological features of type 2 diabetes and its metabolic complications (hyperglycemia, hyperinsulinemia, and insulin resistance) play a crucial role in the development and progression of both heart failure and cognitive dysfunction. This connection has opened to a potential new strategy, in which new classes of anti-diabetic medications, such as glucagon-like peptide-1 receptor (GLP-1R) agonists and sodium-glucose cotransporter 2 (SGLT2) inhibitors, are able to reduce the overall risk of cardiovascular events and neuronal damage, showing additional protective effects beyond glycemic control.The pleiotropic effects of GLP-1R agonists and SGLT2 inhibitors have been extensively investigated.They exert direct and indirect cardioprotective and neuroprotective actions, by reducing inflammation, oxidative stress, ions overload, and restoring insulin signaling. Nonetheless, the specificity of pathways and their contribution has not been fully elucidated, and this underlines the urgency for more comprehensive research.